Impact Of Service Inovation Behaviour On Service Development In Hospitality Industries (Research On Hotels & Restaurant In East Java Indonesia) - Zainul Wasik; MahjudinMahjudin; Kuncoro Catur Nugroho; Dody Suhermawan (PT. Mawadaku Sukses Solusindo, 2023)
The ability to inovate is very important task for a multinational hotel where this is the main goal is to get a competitive advantage, which allows them to provide services that exceed customer expectations. Service innovation capabilities also contribute to hotel competitive advantage, however, there is very little research exploring ways to improve service innovation capabilities. In addition, while social capital fosters the power of innovation, research on the process of transforming available resources embedded in social interactions into actual service innovation capabilities is also limited. Thus, the aim of this study is to investigate the effect of social capital on the ability of service innovation through knowledge sharing in the hospitality industry. The sample used in this study is the hotel industry, especially hotels with 4 or 5 stars in East Java, the results of this study indicate that sharing knowledge mediates the effect of social capital on the ability of service innovation and knowledge sharing is a mechanism for transforming social capital innovation into service innovation capabilities